Monitoring suplai Listrik Berbasis SMS Gateway Bandara Halu Oleo - Hanika Pasang; Gamal Abdel Nasser; Sahabuddin Hay; Waode Zulkaidah; St. Nawal Jaya (Program Pendidikan Vokasi Teknik Mesin, 2022)
In a flight process requires many systems that are required to work properly so that in the flight process there are no obstacles or damage that causes accidents that can be detrimental from all aspects, especially the loss of human life. Aviation safety facilities must be alive for 24 hours, so that if there is a power cut from PLN, the UPS (Uninterruptible Power Supply) as a backup that provides electricity supply will work automatically to provide supply to the aircraft communication system to keep it alive. However, UPS only lasts 30 minutes to supply electricity to the load and sometimes if problems occur such as loss of electricity supply from PLN, generators or UPS, the aircraft communication system at Halu Oleo airport will be very disrupted. Therefore, so that the aircraft communication system continues to live, a system is created that can help the Halu Oleo airport Navigation Telecommunication Technician in controlling the electricity supply in the airport tower halu oleo so that it does not die. In the early stages thepins Input and Output will initialize what is needed. must be done, then the current sensor will read how much current is entering the UPS load if the current has been read, the system from the GSM module will send the message SUPPLY CONNECTED LOADS but if the current is not read by the current sensor then the GSM module will send a message that the load SUPPLY is disconnected and The buzzer will flash intermittently for 10 minutes. If within 10 minutes there is no action from the technician, the system will automatically make a telephone call.